The Effectiveness of Loyalty Programs in Driving Customer Retention in Fashion Retail: A Systematic Literature Review - Rachman, Adryan; Efawati, Yen; Daniswara, Muhammad Daffa (International Journal Administration, Business & Organization, 2025)
The digital transformation of the fashion retail sector has redefined customer-brand relationships, emphasizing the need for loyalty strategies that transcend traditional transactional approaches. This study, a systematic literature review (SLR), evaluates the effectiveness of loyalty programs in enhancing customer retention. A total of 201 peer-reviewed international articles were analyzed using bibliometric visualization with VOSviewer and thematic synthesis within the PRISMA framework. The analysis, guided by the Commitment-Trust Theory and the Customer-Based Brand Equity (CBBE) model, revealed that customer loyalty is no longer driven solely by incentives such as points or discounts. Instead, it is increasingly shaped by emotional engagement, personalized digital experiences, and the integration of social and environmental values into brand narratives. Gamification techniques and AI-powered personalization emerged as key enablers of long-term customer relationships. These findings have significant theoretical and practical implications, underscoring the importance of designing omnichannel, user-centric, and socially relevant loyalty programs to sustain customer retention in the highly competitive fashion retail landscape. Challenges remain in the complexity of program designs and their alignment with the preferences of younger generations, such as Millennials and Gen Z. Future research should consider adopting mixed-method and longitudinal approaches to gain a more comprehensive understanding.